The Development of Social Climate in Virtual Learning Discussion Groups - Oren, Avigail; Mioduser, David; Nachmias, Rafi (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
As the educational use of computer mediated communication (CMC) increases there is growing interest among researchers as to social processes evolving within the varied models of group work using Internet, e.g., special interest groups, topical discussion groups, discussion forums attached to virtual courses, and learning communities. In this paper we present a synthetic summary of five studies that explored social climate issues in synchronous and asynchronous online activities in academic courses, focusing on the following questions: Does a social atmosphere develop in online learning discussion groups? What are the different modes of social interaction are manifest in online learning discussion groups? What is the role of the virtual teacher with regards to the social climate in online learning discussion groups? Discussed are the implications of these five studies' on the design of virtual-learning-discussion-groups, and the results for the characterization of teacher moderation functions.